História da educação profissionalizante: práticas e representações sociais da Escola Estadual Américo Renê Giannetti 1977 - 1996 - Resende, Karla Patrícia (2005)
This research was inserted in the field of investigation of the Education History. More specific field in the area of the Education Institutions History. The study object was the State School Américo Renê Giannetti, headquartered in Uberlândia - MG. The object of this research was to focus certain practices and representations built on the vocational technical teaching of the Second degree (2o Grau) in the referred school, in the period from 1977 to 1996. The research analyzed the local singularities, establishing a dialogue with historical and theoretical bases, looking for interrelations with the larger subjects of the Brazilian education, detaching the vocational teaching. For that investigation was consulting a bibliography regarding theme, as well as, documents of the file in the school, Municipal Public file, pictures and former-students' collected depositions, former-teachers and former-director of the school. The reached results demonstrated that the practices and representations of the school meditate, in relation to formation vocational technical, they legitimated attempts of maintenance of this teaching. Through that idea spread by the same that the project was to form the student for the work, it idealizes this work and incorporate in a positive way for some and negative for others of the school subjects.